Student politics and the fight for democracy in the 80s in the Southern Cone. How the transition mode affected party identities and the organization of the university student movement - Palacios-Valladares, Indira (CIAN-Revista de Historia de las Universidades, 2024)
This article examines an understudied topic: how the mode of democratic transition affects the presence of party identities and organics within social movements. It does so through a qualitative comparative analysis of university student movements in Argentina, Chile, and Uruguay during the 1980s’ transitions from military rule to democracy. Based on an indepth analysis of secondary literature, the article argues that while the transition reinvigorated student political organization across the three countries, differences in the mode of transition produced cross-national variation in movement partisan dynamics. More specifically, in Chile, where the transition occurred through an elite transaction pact, student movement party identities and organizations weakened. The opposite was true in Argentina and Uruguay, where democratic transitions resulted from regime defeat and extrication, respectively.